Diagnostic Accuracy of 3-Dimensional Endoanal Ultrasound in Identifying Perianal Crohn's Fistulas. Issue 8 (August 2018) - Luglio, Gaetano; Giglio, Mariano Cesare; Rispo, Antonio; Bucci, Cristina; Sollazzo, Viviana; Castiglione, Fabiana; De Palma, Giovanni Domenico; Bucci, Luigi
Abstract : BACKGROUND: Perianal fistulizing Crohn's disease is a challenging clinical situation that requires proper management. Some features seen on the endoanal ultrasound can be helpful in discriminating between cryptoglandular and Crohn's disease fistulas. OBJECTIVE: The aim of this study was to define the diagnostic accuracy of 3-dimensional endoanal ultrasound in differentiating between Crohn's disease and cryptogenic fistulas. DESIGN: This was a prospective observational study. SETTINGS: The study was conducted in the colorectal unit of an IBD referral center. PATIENTS: Consecutive patients referred for suspected perianal sepsis from September 2015 to December 2016 were included. INTERVENTIONS: Three-dimensional endoanal ultrasonography was the studied intervention. MAIN OUTCOMES MEASURES: Sensitivity, specificity, and positive and negative likelihood ratios of 4 ultrasonographic features (Crohn's ultrasound fistula sign, the presence of a double track, debris or an abscess within the fistula track, and the maximum width of the track) in discriminating between cryptoglandular and Crohn's disease fistulas were calculated. The interobserver agreement for each feature was quantified. RESULTS: In this study, 158 patients, of whom 33 had a diagnosis of Crohn's disease, were included. The interobserver agreement was good for all of the ultrasonographic features. All of these features were more frequent in cases of Crohn's disease fistulas ( p = 0.0001). The maximum width of the fistula track was highly accurate for discriminating between cryptogenic and Crohn's disease fistulas (area under the receiver operating characteristic curve = 0.922). The simultaneous presence of 2 features was suggestive of Crohn's disease fistula. In particular, the presence of a track width >4 mm in conjunction with either a double track or the Crohn's ultrasound fistula sign showed very high specificity (1.00). Conversely, a fistula track width ⩽3 mm had high sensitivity (0.97). LIMITATIONS: Patients included in the cryptogenic group might be diagnosed as having Crohn's disease at follow-up. CONCLUSIONS: The combination of specific endoanal ultrasonographic features allows for highly accurate discrimination between Crohn's disease and cryptogenic fistulas. SeeVideo Abstract athttp://links.lww.com/DCR/A619 . Abstract : Supplemental Digital Content is available in the text.